Performance Human Resources Of Owners Micro And Small Businesses In The Upgrading MSMEs Program, Bogor District - Warcito, Warcito; Akbar, Maruf; Hamidah, Hamidah (Jurnal Manajemen, 2020)
This study aims to determine the performance of the human resources of micro and small business owners in improving MSMEs to upgading. This study uses a qualitative descriptive approach, micro and small business owners in Bogor Regency. Respondents were chosen purposely, namely 100 micro and small business owners who participated in the Micro and Small Business Consultation Clinic in Bogor Regency. The purpose of doing entrepreneurial activities is to get profits that are used to improve the family economy. The results showed that the performance of human resources was related to the characteristics of micro and small business owners from age, education, other occupations, as well as characteristics of micro and small businesses which included types of products, business forms, business legality, and length of business. business and the number of workers. All respondents have attended new entrepreneurship training (WUB), 57% of food security extension technical guidance (PKP) and business management training (56%). This proves that increasing the capacity of business owners is very important to do both independently, government programs and corporate CSR programs for business continuity.